HUBUNGAN KEBERSIHAN DIRI DENGAN KEJADIAN INFEKSI ENTEROBIUS VERMICULARIS PADA ANAK USIA 2 – 10 TAHUN DI RUMAH SUSUN PENJARINGAN - Natasha Gabby Ratimanjari; Hanna Yolanda (Bahasa Indonesia, 2019)
Introduction: Development of medicine in Indonesia goes along with the diseases that emerged from lifestyle. Prevention can be done by implementing clean and healthy life protection (PHBS). One of the diseases that can occur due to lack of PHBS is worm infection. One of the worms that often infects children is Enterobius vermicularis. This study was conducted to assess the relationship between personal hygiene and E. vermicularis infection. Methods: This is a cross-sectional study with data taken from 110 children (2-10 years) with parents / guardians at Rumah Susun Penjaringan, North Jakarta. The independent variable of this study is personal hygiene and the dependent variable is E. vermicularis infection in children that uses data from questionnaires and lab exams. Results: The study was attended by 110 respondents. It is found that more than 80% of respondents wash their hands with soap before eating, wash their hands with soap after using the toilet, do not scratch the anus at night, routinely clip nails at least once a week, and use footwear while playing outdoors. More than 90% of respondents change their bed sheets regularly and took a bath twice a day. All respondents bathed using clean water and soap. More than 70% of respondents do not bite their nails, wash their hands after going to play, and consume anthelmintics. More than 50% of respondents do not wear other people's underwear. The results of the laboratory study found no E. vermicularis eggs. Conclusion: There is no infection of E. vermicularis in children age 2 – 10 at Rumah Susun Penjaringan